Analysis of Cardiovascular Risk Factors in Adults with Congenital Heart Disease - Moon, Ju Ryoung (Korean Circ J, 2015)
BACKGROUND AND OBJECTIVES: The objective of this study was to analyze cardiovascular risk factors in adults with congenital heart disease (ACHD). SUBJECTS AND METHODS: The subjects for this study comprised 135 patients, aged 18 years and above, who visited the ACHD clinic at the Samsung Medical Center and 135 adults with a structurally normal heart who were randomly selected from the Center for Health Promotion during the same period. For the analysis, the ACHD group was further divided into an ACHD group that underwent correction by cardiac surgery and a cyanotic group. RESULTS: The mean (standard diviation) age (years) of patients in the surgically corrected group was 48.4 (10.9) years, while that of patients in the cyanotic group was 43.1 (9.0) years and that of patients in the control group was 47.1 (10.3) years (p=0.042). The adjusted odds ratios (ORs) for past smoking, hypertension, diabetes mellitus, hypercholesterolemia, obesity, and metabolic syndrome were significantly higher in the surgically corrected patients than in the controls. However, the ORs for all variables excluding past smoking were significantly lower in the cyanotic group compared with the control group. After adjustment for age, gender, smoking, alcohol use, and exercise, the ORs for metabolic syndrome were 0.46 (0.35-0.57, p<0.001) and 1.48 (1.14-1.92, p=0.003) in the cyanotic and surgically corrected groups, respectively. CONCLUSION: Cardiovascular risk factors need to be considered in surgically corrected ACHD patients as well as in adults with a structurally normal heart. A further study with a long-term follow-up is needed for developing guidelines for prevention.